PERANCANGAN SISTEM INFORMASI TERINTEGRASI UNTUK MENGELOLA DATA AGENCY DISTRIBUTOR, DAN REBATE MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Itkonul Akbar; Panca RioNugroho; Rizky Reksa Nugraha Firmansyah; Saprudin (Journal of Research and Publication Innovation, 2025)
This research was conducted as one of the academic requirements to complete studies in the Informatics Engineering Study Program, Faculty of Computer Science, Pamulang University. This research activity aims to design an integrated information system to manage agency, distributor, and rebate data using the Rapid Application Development (RAD) method at PT International Paint Indonesia. This system is designed to help the administration process of agency, distributor data, and rebate calculations more efficiently and accurately compared to the manual system previously used. The application was developed using the Java programming language with the UML (Unified Modeling Language) approach, including use case diagrams, activity diagrams, sequence diagrams, and ERD (Entity Relationship Diagrams), and utilizing the MySQL database for data storage. During the implementation of the research, the author conducted an analysis of user needs through direct interviews with related parties at PT International Paint Indonesia, designing the application interface, creating a database, and implementing features such as adding, editing, and deleting agency and distributor data, as well as rebate data management. After going through the functionality testing stage, the system was proven to be able to replace inefficient and error-prone manual processes, as well as providing easy access to data quickly and safely. The final result shows that the system created is able to improve the efficiency of the agency, distributor, and rebate data management process, minimize the risk of data loss or error, and provide an integrated digital solution for PT International Paint Indonesia.